The Impact of the News on Children and Children’s Perception of the News - Akyüz, Mehmet Hanifi; Özmen, Meryem; Polatlar, Duygu Yalman (Akdeniz University, 2024)
The research aims to examine the impact of watching the news on children in line with the answers received from them. In the research conducted in the phenomenological design, interviews were conducted through a semi-structured interview form created by getting expert opinion. The data obtained after the interviews with 105 children between the ages of 6 and 8 were analyzed with the descriptive analysis method. Consistent with the purpose of the research, the following themes were obtained from the data: "the purpose of the news", "the meaning of the news", "the emotional impact of the news" and "the news and the family". As a result of the research, it has been concluded that the news has a positive purpose but a negative meaning for most of the children, the color that attracts attention is red, the news that makes children sad is more, and the families watch the news unresponsively. The research provides significant clues for researchers, educators and families working on media literacy and child development.

Araştırma haber izlemenin çocuklar üzerindeki etkilerini çocuklardan alınan cevaplar doğrultusunda incelemeyi amaçlamaktadır. Fenomenolojik desende yürütülen araştırmada, uzman görüşü alınarak oluşturulan yarı yapılandırılmış görüşme formu aracılığıyla görüşmeler yapılmıştır. 6-8 yaş arasındaki 105 çocuk ile yapılan görüşmeler sonrasında elde edilen veriler betimsel analiz yöntemiyle analiz edilmiştir. Araştırmanın amacıyla tutarlı olacak şekilde verilerden şu temalar elde edilmiştir: “Haberin amacı”, “haberin anlamı”, “haberin duygusal etkisi” ve “haber ve aile”. Araştırmacıların birbirinden bağımsız olarak yapmış oldukları her temaya ait kategoriyi temsil edecek kodlamalar arasında iç tutarlılığı belirlemek için Miles ve Huberman modeli kullanılarak güvenirlik analizi yapılmıştır. Araştırma sonucunda çocukların çoğunluğu için haberlerin olumlu bir amaç ama olumsuz anlam taşıdığı, dikkat çeken rengin kırmızı olduğu, üzen haberlerin daha fazla olduğu, ailelerin haberleri tepkisiz bir şekilde izlediği sonucuna ulaşılmıştır. Araştırma, medya okuryazarlığı ve çocuk gelişimi konularında çalışmalar yürüten araştırmacılara, eğitimcilere ve ailelere yönelik önemli ipuçları sağlamaktadır.
Haberlerin Çocuklar Üzerindeki Etkisi ve Çocuklardaki Algısı
Keywords: Child; News; Television; Family; Parental Mediation; Çocuk; Haberler; Televizyon; Aile; Ebeveyn Arabuluculuğu